2016
DOI: 10.1002/ldr.2606
|View full text |Cite
|
Sign up to set email alerts
|

Maintain Spatial Heterogeneity, Maintain Biodiversity—A Seed Bank Study in a Grazed Alpine Fen Meadow

Abstract: Wetland degradation is a source of anxiety and is more severe in cold regions than other areas. The soil seed bank acts as a propagule source for revegetation to affiliate the restoration of degraded wetlands. However, the effects of this approach are controversial and depend on the traits of the seed bank and its interactions with the environment. The seed bank in an alpine fen meadow was studied to determine its exact role in revegetation. The surveyed shore of a Tibetan lake, Gahai Lake, was divided into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 91 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…The β-diversity of the above-ground vegetation and soil seed bank declined under high N treatments because of a homogenized environment and directional environmental filtering. We found that environmental heterogeneity decreased with increasing N addition, which promotes the chance of colonization of the same species or species with similar characteristics (Xu et al, 2017). Therefore, species composition became more similar and β-diversity consequently decreased.…”
Section: Discussionmentioning
confidence: 76%
“…The β-diversity of the above-ground vegetation and soil seed bank declined under high N treatments because of a homogenized environment and directional environmental filtering. We found that environmental heterogeneity decreased with increasing N addition, which promotes the chance of colonization of the same species or species with similar characteristics (Xu et al, 2017). Therefore, species composition became more similar and β-diversity consequently decreased.…”
Section: Discussionmentioning
confidence: 76%
“…In general, drainage leads to more similar water table depths across the ecosystem, which hinders the creation of resilient ecological niches 53 . A lesser variety of microforms tends to lead to lower biodiversity and, oftentimes, to a dominance of vascular plants [54][55][56][57] .…”
Section: Peatland Resiliencementioning
confidence: 99%